EMERGENCY RESPONSE SERVICES IN PESHAWAR - Sofia Shehzad (Gandhara University, 2015)
The recent terror attacks on Army Public School and Imam Bargah in Hayatabad, Peshawar once again highlighted the continuing fragile law and order situation that the country is facing in general and the province of KPK in particular. The civilian emergency response mounted to these events and those of a similar nature in the past can at best be described as grossly insufficient and well below the desired standards.  Having been at the heart of 'war on terror", and faced with numerous bomb blasts and other forms of militant activities over successive years in the recent past, one would expect a mature and systematic approach inculcated in the country's response to emergency. Sadly this has not been the case and the same chaos and indifference by the concerned authorities is seen at the site of occurrence, during transportation and in the hospitals as was the case before these events were a regular feature. To add to the spectrum of these woes is the lack of any coordinated efforts to rehabilitate the victims either psychologically, physically or financially. As I searched for an effective system globally adopted for disaster management of various scales, I came across the existence of various national and international organizations tasked to ensure preparedness and swift response in event of any such eventualities.  International  organizations such as   Red Cross, The International Emergency Management Society (TIEMS), The International Recovery Platform (IRP) and United nations organization  help reduce vulnerability and assist cope with natural disasters such as floods and earthquakes, industrial sabotage and other incidences of significant humanitarian crisis. While some of these organizations may help creating awareness and offer technical guidance in managing manmade disasters, they have a very limited role in practically addressing incidents related to localize events of terrorism. This responsibility is borne by respective governments in light of the prevailing law and order situation and resource availability. Different countries then have other umbrella organizations overlooking management of emergency situations arising from terror related disasters in addition to natural calamities eg the Civil Contingencies secretariat in UK, the Federal emergency management authority in US and the National disaster response force in India. In Pakistan unfortunately there is no concept of an organized response to events resulting in multiple or mass casualties, be it a result of any major accident or an act of terrorism. Organizations such as APDMA and PDMA have limited roles dealing mainly with natural disasters. Need of the hour is for an organization or team to cater for manmade disasters given the recent frequency of these events. In the absence of any responsible organization taking the lead and developing protocols as well as providing guidelines, the workforce available for pre hospital and hospital-based critical care varies enormously. Every major city of the country and specially Peshawar should have a disaster control management plan involving security agencies, paramedic and ambulance services and all major hospitals who should develop an effective strategy to facilitate management of injured patients.   An effective approach would depend on the ability of the concerned team to anticipate, assess, prevent, prepare, respond and recover from an incident. Security agencies must cordon off the site of incident allowing only emergency vehicles and personnel to approach the site once secured. The hospital nominated to receive the brunt of casualties should be informed well in time for emergency preparedness. If possible all unnecessary traffic flow in the vicinity of the hospital should be diverted according to a predetermined plan.  The Accident and Emergency departments should have a viable communication system of summoning their trauma team and any additional staff needed according to the nature and magnitude of the calamity on a very short notice.  Within the hospital all visitors and well wishers as well as media personnel and politicians should be restricted to nominated zones with facilities of a public address system and an information centre updating the list of injured and dead at regular intervals. A spacious TRIAGE hall with designated triage officers (doctors or nurses) should be at hand to sort out the patients and prioritize their treatment according to the nature of their injuries and resources available. The major hospitals must build up their capacity in terms of skilled manpower and equipment/medicine and be ready for any major incident in its catchment area besides being able to receive a spill over in case of any major disaster in adjoining vicinities. Doctors and other support staff in ER should be familiar with the basic principles of Emergency life saving measures. It should be mandatory for the aforementioned to have attended trauma management courses such as Advanced Trauma Life Support, Primary Trauma Care or Emergency Room Trauma Care. There is considerable evidence to show that properly trained staff can make a marked difference when it comes to saving precious lives. There should also be appropriate arrangement for dealing with bodies of dead victims and counseling their near and dear ones. No doubt, considerable effort and commitment is needed if the above goals have to be achieved. To ensure a well organized and coherent response to any major incident there has to be a lead body running the show. All those involved in emergency management from the scene of the incident to the hospital receiving and managing the injured patients should be part of a team and should be allowed to interact on a regular basis through seminars and conferences framing and developing their own standard operating procedures and guidelines. Effective emergency management has been and will always be the crunch requirement of any civilized society and it is imperative that the government should take practical steps in addressing this issue in the best interest of the public.